2019
DOI: 10.1111/clr.13412
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported outcome measures (PROMs) and maintenance events in 2‐implant‐supported mandibular overdenture patients: A 5‐year prospective study

Abstract: Objective To prospectively evaluate patient‐reported outcome measures (PROMs) and treatment outcomes of mandibular two‐implant retained overdentures (IOD) in an edentulous geriatric cohort with history of deficient complete dentures (CD). Materials and Methods A total of 103 patients with deficient CD received new optimal CD. After a period of 3 months, 80 of the patients voluntarily received IOD. Outcomes collected at pre‐, post‐CD/post‐IOD treatment annually up to 5 years, included (a) Clinical outcomes: den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 41 publications
0
16
0
1
Order By: Relevance
“…More recently, Feine et al, 35 as part of Group 3 of the 6th ITI Consensus Conference concluded that in general, patients are very satisfied with the esthetics of implant-supported restorations and the surrounding mucosa. 36 The current findings suggest that certain patient opinions, perceptions, and characteristics related to oral hygiene measures are significantly associated to the diagnosis of the peri-implant condition. In general, these factors seem to discriminate between healthy conditions and PM, and thus between health and disease.…”
Section: Agreements and Disagreements With Previous Studiesmentioning
confidence: 66%
See 3 more Smart Citations
“…More recently, Feine et al, 35 as part of Group 3 of the 6th ITI Consensus Conference concluded that in general, patients are very satisfied with the esthetics of implant-supported restorations and the surrounding mucosa. 36 The current findings suggest that certain patient opinions, perceptions, and characteristics related to oral hygiene measures are significantly associated to the diagnosis of the peri-implant condition. In general, these factors seem to discriminate between healthy conditions and PM, and thus between health and disease.…”
Section: Agreements and Disagreements With Previous Studiesmentioning
confidence: 66%
“…and Yao et al., 34 where patient satisfaction improved significantly in all the studied domains after the completion of treatment. More recently, Feine et al., 35 as part of Group 3 of the 6th ITI Consensus Conference concluded that in general, patients are very satisfied with the esthetics of implant‐supported restorations and the surrounding mucosa 36 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…47 Takahashi ve arkadaĢlarının ball, locator ve mıknatıs tutucuların makaslama gerilimlerini kıyasladıkları çalıĢmada 48 en düĢük makaslama kuvvetinin manyetik tutucuda; en yüksek makaslama kuvvetinin ball tutucuda olduğu bildirilmiĢtir. Zhang ve arkadaĢlarının mıknatıs ve locator tutucuları kıyasladıkları çalıĢmada 49 en fazla komplikasyonun ilk yılda görüldüğü ve mıknatıs tutucuda daha fazla komplikasyon olduğu bildirilmiĢtir.…”
Section: -Mıknatıs Tutucularunclassified